Transcriptional and post-transcriptional control of eEF1A2 expression during myoblast diffrerentiation - Vislovukh, A.A.; Groisman, I.S.; El’skaya, A.V.; Negrutskii, B.S.; Polesskaya, A.N. (Вiopolymers and Cell, 2012)
During postnatal development, the switch of the expression from isoform A1 to the isoform A2 of eukaryotic translation elongation factor (eEF1A) is observed in neuronal and muscle tissues. The switch of the expression is a vital fundamental process, as mutant mice, with the partial EEF1A2 deletion dies on the 28th day after birth. Mechanism of the inhibition of A1 and stimulation of A2 expression during the first days of postnatal development is unknown. The existence of potential miRNA binding sites in the 3’UTR of mRNAs encoding the isoforms assumes a post-transcriptional control of abovementioned phenomenon. Aim. To check the possibility of post-transcriptional regulation of the isoforms A1 and A2 expression during differentiation of the human immortalized myoblasts cell line LHCN. Methods. The level of gene expression was quantified by qPCR, the existence of post-transcriptional regulation was demonstrated with Dual-Luciferase® Reporter Assay. Results. Using immortalized human myoblasts cell line LHCN, the induction of isoform A2 of eEF1 during differentiation of myoblasts was shown. The existence of transcriptional and post-transcriptional control of the abovementioned process was confirmed. Downregulation of mir-661 and mir-744 that have binding sites in the 3’ UTR of EEF1A2 mRNA, during differentiation suggests a potential role of microRNAs in the eEF1A2 induction during myoblast differentiation. Conclusions. Induction of A2 isoform of eEF1 during differentiation of myoblasts occurs on transcriptional and post-transcriptional level.
Keywords: eEF1A1, eEF1A2, immortalized human myoblasts LHCN, differentiation, microRNA. Abstract
У процесі постнатального розвитку в нейрональній і м’язовій тканинах відбувається зміна ізоформи А1 фактора елонгації трансляції на ізоформу А2. Перемикання експресії ізоформ є життєво важливою подією, оскільки мутантні миші, що містять делецію EEF1A2, гинуть на 28-й день після народження. Механізми інгібування А1 і стимуляції А2 протягом перших днів постнатального розвитку невідомі. Наявність сайтів зв’язування мікроРНК у 3'-нетрансльованих послідовностях мРНК ізоформ фактора елонгації трансляції передбачає існування посттранскрипційного контролю даного процесу. Мета. Перевірити можливість посттранскрипційної регуляції експресії ізоформ А1 і А2 під час диференціації імморталізованих міобластів людини LHCN. Методи. Рівень експресії генів визначали методом кількісної ПЛР, наявність посттранскрипційного контролю детектували методом репортерних генів. Результати. Використовуючи як модель клітинну лінію імморталізованих міобластів людини LHCN, показано індукцію ізоформи А2 фактора елонгації трансляції eEF1 при диференціації міобластів, наявність транскрипційного і посттранскрипційного контролю в даному процесі, а також потенційну участь мікро-РНК у процесі зміни експресії ізоформ. Висновки. Індукція ізоформи А2 протягом диференціації міобластів може відбуватися як на транскрипційному, так і на посттранскрипційному рівні.
Ключові слова: eEF1A1, eEF1A2, імморталізовані міобласти людини LHCN, диференціація, мікроРНК.